Justice and discretion in the law of unjust enrichment. (September 2019) - Hedley, Steve
The academic theory of unjust enrichment, hypersensitive to charges that it represents 'palm-tree justice', aspires to a high degree of rigour and conceptual unity. The judiciary, while highly receptive to that theory, are nonetheless subject to the demand to do substantial justice in individual cases. This article reviews that tension in contemporary theory and case law. Firstly, it reviews the failure, to date, of theories seeking to justify modern unjust enrichment theory. Next, it notes the increasing rigidity of that theory. Then it reviews recent case law, where judges have evidently allowed other considerations to guide the application of theory. Finally, the article suggests that we have reached the stage where any apparently unfair claim in unjust enrichment will be refused whether or not that unfairness can find a niche in current theory, thus effectively making the liability subject to a judicial discretion.